Facilitation and Understanding in Hadith Studies - Klaina, Mekki (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2024)
This study holds significant importance as it investigates the various challenges that students face in comprehending academic texts, particularly in the study of Hadith in non-Arabic speaking countries. The main objective of this study is to identify the factors contributing to students' difficulties in mastering the subject, such as weak language skills, lack of practical application, and limited access to original sources. A key issue in this context is the students' reliance on memorization rather than deep understanding. The study employs a qualitative approach, drawing on the researcher's personal experience in Morocco, the United Arab Emirates, and Qatar, along with observations of students at Sultan Sharif Ali Islamic University. The findings reveal that insufficient Arabic language education, coupled with inadequate emphasis on discussion skills, has contributed to the difficulties in understanding the Hadith sciences. As a result, the study recommends a more balanced distribution of the curriculum across all academic years, greater use of primary sources in teaching, and increased practical training in Hadith studies to enhance students' comprehension of the subject. Moreover, it is advised to increase the credit hours allocated to Hadith sciences and Takhreej to ensure better understanding.